Indicators of self-reported human immunodeficiency virus risk and differences in willingness to get tested by age and ethnicity: An observational study. Issue 31 (August 2018) - Brown, Brandon; Marg, Logan; LeComte-Hinely, Jenna; Brinkman, David; Zhang, Zhiwei; Sullivan, Greer
Abstract : Abstract: There are many barriers that prevent people from receiving human immunodeficiency virus (HIV) testing; however, little is known about the impact of age and ethnicity on HIV testing. We explored differences in self-reported HIV risk and willingness to be tested in the 2014 Get Tested Coachella Valley Community Survey by age and ethnicity. Data were collected from 995 participants via survey methods (online, hard copy, and in person). Surveys asked about demographics, sexual history, HIV testing history, thoughts on who should get tested, and future preferences for HIV testing. Most participants were women (62.5%), Hispanic (55.8%), and older than 50 years (51%). Participants who did not receive testing said they did not do so because they did not perceive themselves as at risk of contracting HIV (51.8%). Many participants (24.1%) said they did not receive testing because their health care provider never offered them the HIV test. Participants were more likely to have been tested if they were between 25 and 49 years old, compared to participants aged 50 or older (70.2% vs 48.6%, respectively, P < .001). Participants who were not Hispanic or Latino were more likely to have had an HIV test compared to Hispanic or Latino participants (62.5% vs 51.1%, P < .001). Interventions are needed to reach older adults to address HIV testing and beliefs. These interventions must debunk beliefs among physicians that older adults are not sexually active and beliefs among older adults that only certain populations are at risk of HIV.